258 Promoting Academics and Community Engagement (PACE): A Protocol on the ScienCE of Community Engagement in Clinical and Translational Science - David Cordova; Karen Calhoun; Tricia Piechowski; Mary Beth Damm; Barbara Israel; Sarah Bailey; Erica E. Marsh; Y. Gipson Allen (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: The Michigan Institute for Clinical & Health Research Community Engagement (MICHR CE) has collaborated for 15+ years with underserved communities on public health issues. As Michigan’s sole CTSA institution, we aim to advance the science of community engagement in translational science statewide. METHODS/STUDY POPULATION: MICHR CE PACE (Promoting Academic-Community Engagement) will advance clinical and translational science. Key steps include: 1) form a PACE Steering Committee; 2) PACE Trainings with community-academic partner Detroit Urban Research Center; 3) PACE Training Manual; 4) community Grand Rounds to bridge academic-community insights; and 5) community resources (e.g., toolkits). PACE projects will spotlight community-engaged research (CEnR) via diverse media including social media and community-level communications. The PACE ScienCE initiative will embody cultural humility by addressing power imbalances, emphasizing trust. We will utilize assessments and root cause analyses to navigate CEnR barriers. RESULTS/ANTICIPATED RESULTS: Anticipated results from MICHR CE’s planned approach with PACE include strengthened academic-community relationships. Formation of the PACE Steering Committee and collaborations are expected to foster more structured and impactful CEnR trainings. The PACE Training Manual will become a foundational resource for CEnR best practices. Community Grand Rounds will reveal increased interdisciplinary insights and community trust. All PACE projects will utilize diverse media to enhance CEnR visibility and community-level access. Lastly, by addressing power disparities via PACE ScienCE, we foresee enhanced trust, reduced barriers, and more transparent community-academic collaborations. DISCUSSION/SIGNIFICANCE: This strategy, based on co-planned efforts and community consultations, aims to reshape Michigan’s CEnR landscape and offers a replicable model for other regions. The insights gained will guide community-academic collaborations promoting translational, inclusive, and efficient community engagement.